A methodological approach for assessing cross-border supply chain exposure to climate change impacts on crop production and transport - Emilie Stokeld; Chris West; Simon Croft; Lindsay C. Stringer; Cornelia Auer (Climatic Change, 2026)

New U-series dates on the Petralona cranium, a key fossil in European human evolution - Christophe Falguères; Qingfeng Shao; Christian Perrenoud; Chris Stringer; Olivier Tombret; Lisa Garbé; Andreas Darlas (Journal of Human Evolution, 2025)

A Middle and Late Devensian sequence from the northern part of Kents Cavern (Devon, UK) - Rob Dinnis; John Boulton; Barry Chandler; Jesse Davies; Jennifer C. French; Thomas Higham; Louisa Jáuregui; Mark Lewis; Matthias Meyer; Danielle Schreve; Chris Stringer; Chris Proctor (Journal of Quaternary Science, 2025)
1920s/30s excavation of a Middle Devensian sequence in the northern part of Kents Cavern recovered important Late Middle and Early Upper Palaeolithic archaeological material, including Britain's oldest known Homo sapiens remains. Questions remain about this material, including how it came to be in the cave. Judged by the recorded distribution of finds it may have entered via the Northeast Gallery. A previously unrecorded entrance into the cave from the Northeast Gallery was identified in 2014, and a column through the entrance's sedimentary fill was excavated during 2015–2016. The results of that work are reported here. The entrance retains an intact and well‐stratified Pleistocene sequence comparable to the ‘Cave Earth’ unit described previously inside the cave. The uppermost part of the newly recognised Northeast Gallery entrance sequence has been removed by historical excavation, with most of the remaining sediments spanning the Middle Devensian and earlier part of the Late Devensian. The sequence contains bone and pollen, and ancient mammalian DNA is preserved within the sediments. The base of the Northeast Gallery entrance sequence is formed of a clayey diamict comparable to the cave's ‘Breccia’ unit, a deposit currently understood as Middle Pleistocene, and previously identified only in Kents Cavern's southern chambers. Comparison of the excavated sequence with the historical record of the Vestibule excavation shows that the basal cave earth deposits in the Northeast Gallery entrance are significantly higher than those inside the cave. Although requiring further work to confirm, this suggests that the Northeast Gallery could have played a major role in the accumulation of material in the Vestibule during the Middle Devensian.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Direct dating of human fossils and the ever-changing story of human evolution - Rainer Grün; Chris Stringer (Quaternary Science Reviews, 2023)

Episodic population fragmentation and gene flow reveal a trade‐off between heterozygosity and allelic richness - Peta Hill; Chris R. Dickman; Russell Dinnage; Richard P. Duncan; Scott V. Edwards; Aaron Greenville; Stephen D. Sarre; Emily J. Stringer; Glenda M. Wardle; Bernd Gruber (Molecular Ecology, 2023)
In episodic environments like deserts, populations of some animal species exhibit irregular fluctuations such that populations are alternately large and connected or small and isolated. Such dynamics are typically driven by periodic resource pulses due, for example, to large but infrequent rainfall events. The repeated population bottlenecks resulting from fragmentation should lower genetic diversity over time, yet species undergoing these fluctuations appear to maintain high levels of genetic diversity. To resolve this apparent paradox, we simulated a metapopulation of constant size undergoing repeat episodes of fragmentation and change in gene flow to mimic outcomes experienced by mammals in an Australian desert. We show that episodic fragmentation and gene flow have contrasting effects on two measures of genetic diversity: heterozygosity and allelic richness. Specifically, fragmentation into many, small subpopulations, coupled with periods of infrequent gene flow, preserves allelic richness at the expense of heterozygosity. In contrast, fragmentation into a few, large subpopulations maintains heterozygosity at the expense of allelic richness. The strength of the trade‐off between heterozygosity and allelic richness depends on the amount of gene flow and the frequency of gene flow events. Our results imply that the type of genetic diversity maintained among species living in strongly fluctuating environments will depend on the way populations fragment, with our results highlighting different mechanisms for maintaining allelic richness and heterozygosity in small, fragmented populations.

Stakeholder perspectives on cross-border climate risks in the Brazil-Europe soy supply chain - Emilie Stokeld; Simon Croft; Tiago N.P. dos Reis; Lindsay C. Stringer; Chris West (Journal of Cleaner Production, 2023)

Aspects of human physical and behavioural evolution during the last 1 million years - Julia Galway‐Witham; James Cole; Chris Stringer (Journal of Quaternary Science, 2019)
This paper reviews some of the main advances in our understanding of human evolution over the last 1 million years, presenting a holistic overview of a field defined by interdisciplinary approaches to studying the origins of our species. We begin by briefly summarizing the climatic context across the Old World for the last 1 million years before directly addressing the fossil and archaeological records. The main themes in this work explore (i) recent discoveries in the fossil record over the last 15 years, such as Homo naledi and Homo floresiensis ; (ii) the implications of palaeogenetics for understanding the evolutionary history of, and relationships between, Neanderthals, Denisovans and Homo sapiens ; (iii) the interplay between physiology and metabolic demand, landscape use, and behavioural adaptations in the evolution of morphological and behavioural innovation; and (iv) recent advances in archaeological understanding for the behavioural record, in particular that of the Neanderthals. This paper seeks to provide a broad‐scale, holistic perspective of our current understanding of human evolution for the last 1 Ma, providing a reference point for researchers that can be built upon as new discoveries continue to develop the landscapes of human evolution. © 2019 The Authors. Journal of Quaternary Science Published by Wiley Periodicals, Inc.

Handaxe and non‐handaxe assemblages during Marine Isotope Stage 11 in northern Europe: recent investigations at Barnham, Suffolk, UK - Nick Ashton; Simon G. Lewis; Simon A. Parfitt; Rob J. Davis; Chris Stringer (Journal of Quaternary Science, 2016)
Britain has an important geological, environmental and archaeological record for Marine Isotope Stage 11 (MIS 11), which makes a major contribution to understanding of the human occupation of northern Europe. New fieldwork at Barnham, Suffolk, UK, has identified through improved geological resolution the change in assemblages from simple core and flake working to those with handaxe technology. The two assemblages are argued to reflect distinct human populations from different source areas in Europe. The paper examines the European record and puts forward a new model of how the complex mosaic of lithic assemblages reflects local, habitual practices during stable environments, but changes in climate and environment led to larger scale shifts in population, resulting in new human groups arriving in Britain.

The morphological affinities of the Middle Pleistocene hominin teeth from Pontnewydd Cave, Wales - Tim Compton; Chris Stringer (Journal of Quaternary Science, 2015)
Seventeen Middle Pleistocene hominin teeth were excavated at Pontnewydd Cave in North Wales between 1980 and 1995 with a probable age of ∼225 ka, associated with handaxe and levallois artefacts. Their Neanderthal characteristics and their affinities with other European Middle Pleistocene teeth and the major sites of Atapuerca‐SH in Spain and Krapina in Croatia are explored. The Pontnewydd teeth are shown to have a marked similarity to those of Atapuerca‐SH, more pronounced than similarities to teeth from other European Middle Pleistocene sites, and to belong in the pre‐Neanderthal stage of Neanderthal evolution. Distinct dental morphological differences between later European Middle Pleistocene specimens, together with those from Atapuerca‐SH, and European Middle Pleistocene Homo heidelbergensis specimens are identified, contradicting the view that both the Pontnewydd and the Atapuerca‐SH fossils belong in that species. Additionally, the similarities in dental morphology between European and non‐European H . heidelbergensis specimens are demonstrated. We argue that when sites are grouped together for comparative purposes this should be done on morphological grounds, and not by apparent date, in view of the possible contemporaneity of European Middle Pleistocene sites that exhibit different degrees of Neanderthal affinities.

Waterjet injection of powdered activated carbon for sediment remediation - Chris J. Redell; Andrew Curtis Elmore; Joel G. Burken; Ryan D. Stringer (Journal of Soils and Sediments, 2011)

History of weta (Orthoptera: Anostostomatidae) translocation in New Zealand: lessons learned, islands as sanctuaries and the future - Corinne Watts; Ian Stringer; Greg Sherley; George Gibbs; Chris Green (Journal of Insect Conservation, 2008)

Recent TIMS dating results from British Late Pleistocene vertebrate faunal localities: context and interpretation - Mabs Gilmour; Andy Currant; Roger Jacobi; Chris Stringer (Journal of Quaternary Science, 2007)
New TIMS dates from British sites underpin and extend the growing model of mammalian faunal history during the Late Pleistocene. The sequence of British faunas during the three successive warm phases of MIS 5 presents a challenging model in which the mammal faunas of the first two temperate phases, 5e and 5c is dominated by species of a classically interglacial character, while that of the final phase, sub‐stage 5a, is dominated by bison and reindeer. This we see as the ‘cold fauna’ appearing in Britain during the cool isotope sub‐stage 5b and subsequently isolated by the rising sea level of isotope sub‐stage 5a. All these three faunas are true island faunas. Copyright © 2007 John Wiley & Sons, Ltd.

Introduction: the Palaeolithic occupation of Europe. A tribute to John J. Wymer, 1928–2006 - Nick Ashton; Simon G. Lewis; Chris Stringer (Journal of Quaternary Science, 2006)